Teachers’ Challenges in Teaching Pronunciation to Preschool Students with Special Needs - Nur Ayu Dwi Hartini (Yayasan Zia Salsabila, 2025)
This qualitative study explores the challenges faced by preschool teachers in teaching pronunciation to children with special needs, focusing on two teachers from a private school in Medan, Indonesia. Data were collected through semi-structured interviews and classroom observations, revealing key issues across three themes: individual student challenges, teaching methodology, and external factors. The study highlights difficulties such as speech delays, motor control issues, and behavioral challenges, which hinder students' pronunciation development. Additionally, teachers reported struggles with inadequate training, time constraints, and large class sizes, which limit the effectiveness of individualized instruction. Parental involvement also emerged as a challenge, with some parents lacking the knowledge to support language development at home. The study suggests that improving teacher training and fostering better collaboration with parents could enhance the learning outcomes for students with special needs. A limitation of the study is the small sample size, and further research with a larger, more diverse group of teachers is recommended to gain broader insights into the challenges of teaching pronunciation in this context.